IMPROVING STUDENT LEARNING IIASIL IN CHRISTIAN RELIGIOUS EDUCATION USING THE COOPERATIVE LEARNING MODEL OF INDEX CARD MATCH TYPE (LOOKING FOR CARD PAIRS) IN CLASS VII-3 SMP NEGERI 1 PAHAE JAE - James Simanjuntak (Universitas Dharmawangsa, 2020)
This research was conducted to find answers to the question, How are the learning outcomes of students in class VII-3 of SMP Negeri 1 Pahae Julu in Christian Religious Education (PAK) learning using the Index Card Match type cooperative learning model (Looking for Pair of Cards) for the 2018/2019 academic year. There are 26 students of class VII-3 SMP Negeri 1 Pahae Julu, 9 girls and 17 boys. The research was conducted in 2 cycles. Research activities were carried out to determine students who completed the Minimum Completion Criteria (KKM) and increased their learning outcomes after using the Index Card Match Type Cooperative Learning Model (Looking for Pair of Cards). KKM for Kriten Religious Education (PAK) class VII-3 SMP Negeri 1 Pahae Julu TP. 2018/2019 is 70 In cycle I and cycle II students use the Cooperative Learning Model Type Index Card Match (Looking for Pair of Cards). The researcher concluded that the learning process using the Cooperative Learning Model Type Index Card Match (Looking for Pair of Cards) in the Christian Religious Education (PAK) subject can improve student learning outcomes in class VII-3 of SMP Negeri 1 Pahae Julu TP. 2018/2019. The initial data of students who completed the KKM were with an average of 57.69% in the poor category and in the first cycle the student learning outcomes increased with an average of students who completed the KKM by 80.76% in good categories, the second cycle increased student learning outcomes with an average of students who completed KKM is 100% very good category.